The strength and deformation behaviour of a residual soil in Singapore - Meng, Guanghui (2010)
Most residual soils in nature are highly structured or cemented depending on the degree of weathering and the formation processes. The shear strength and stress-strain behaviour of residual soil are known to be affected significantly not only by the initial porosity and stress history, but also by the bonds between particles. Although residual soil is commonly encountered during constructions in the tropical region, studies on its engineering properties are far from adequate. There is a lack of in-depth study to characterize the strength and deformation behaviour of intact residual soils in Singapore, especially under more representative testing conditions such as plane-strain conditions.